Lithiophilic Vertical Cactus‐Like Framework Derived from Cu/Zn‐Based Coordination Polymer through In Situ Chemical Etching for Stable Lithium Metal Batteries - Liu, Tiancun; Chen, Shuangqiang; Sun, Weiwei; Lv, Li‐Ping; Du, Fei‐Hu; Liu, Hao; Wang, Yong (Advanced functional materials, 2021)
Detrimental dendritic lithium (Li) growth, infinite volume expansion of Li deposition and inevitable excess electrolyte consumption have always impeded the successful application of Li metal anodes. Herein, a unique lithiophilic vertical cactus‐like framework (LVCF) derived from a Zn/Cu‐based coordination polymer through in situ chemical etching of Cu foam is proposed to enhance the safety and electrochemical performance of Li metal anodes. An ingenious strategy of releasing Cu ions from Cu foam in the presence of organic ligands is implemented successfully to achieve the coordination polymer precursor, resulting in the coexistence of massive lithiophilic nitrogen‐containing functional groups, ZnO quantum dots and in situ grown carbon nanotubes (CNTs) in the LVCF, which is beneficial to avoiding the generation of harmful Li dendrites. Benefiting from the positive effects of the improved lithiophilicity, decreased local current density and relieved volume expansion, LVCF delivers an ultrastable Coulombic efficiency of 98.6% for 600 cycles at 1 mA cm–2 and an improved cycling lifespan of 1800 h for symmetric cells. Full cells comprising LVCF@Li anodes and LiFePO4 cathodes can deliver an ultrahigh capacity of 101.8 mAh g–1 (capacity retention ratio: 77.9%) after 900 cycles at 1 C and excellent rate performance. A 3D free‐standing and lithiophilic vertical cactus‐like framework, commercial Cu foam covered by an annealed Zn/Cu‐based precursor, is proposed as the current collector of Li metal anode. Massive lithiophilic sites (ZnO quantum dots and nitrogen containing groups) and in situ grown carbon nanotubes play a significant role in the suppression of Li dendrites.